An Integrated Sliding Mode and Lyapunov-based Control Approach for Robust Quadcopter Trajectory Tracking - Al Quran, Mahdi; Al-Sheyyab , Ahmad; Rawashdeh, Mustafa; Alheyasat, Abdel rahman (Journal of Engineering and Technological Sciences, 2026)
This paper addresses the challenges of low tracking accuracy in the attitude and position control of quadrotor unmanned aerial vehicles (UAVs). To overcome these issues, a nonlinear hybrid control strategy is proposed by combining adaptive sliding mode control with Lyapunov theory. Accounting for the nonlinearities associated with the coupling among the UAV degrees of freedom, unlike simplified control-oriented models, the proposed strategy is designed to enhance trajectory tracking performance while improving control flexibility and robustness against external disturbances. The proposed strategy expands the validity of the control-oriented model compared with the linear controllers. Moreover, the inherent robustness built into the paradigm of the sliding mode controller improves the robustness against external disturbances as well as uncaptured dynamics within the modeling process. The stability of the system is rigorously analysed using the Lyapunov stability theory, and the results confirm the stability of the proposed controller under various conditions. Extensive simulation tests are conducted to verify the effectiveness and feasibility of the control strategy. The simulation results demonstrate that the proposed method significantly improves tracking accuracy in both attitude and position control, providing a robust and reliable solution for quadrotor UAVs. This hybrid approach ensures precise trajectory tracking while maintaining stability, making it a promising technique for advanced UAV applications.